Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s12663-012-0348-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Neurosensory Changes in the Infraorbital Nerve following Zygomatic Fractures

Abstract: Purpose To evaluate the incidence and recovery of persistent sensory disturbances of the infraorbital (IO) nerve after isolated zygomatic complex fractures with various treatment methods. Methods and ResultsThe study was inclusive of isolated unilateral zygomatic complex fractures and fractures of IO rim .Tests performed were Pin prick and Electrical detection threshold test. The evaluation was done preoperatively, after 1 month and after 6 months of surgery. The results suggested that neurosensory disturbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…They reinforced the advantage of reduction and the practice of miniplate use for the fixation of zygomatic fractures in avoiding sensory deficit of the infraorbital nerve. 23 Our study was consistent with recovery of infraorbital nerve dysfunction following zygomatic fractures were recovery in 74% patients treated with open reduction within 12 weeks.…”
Section: Discussionsupporting
confidence: 89%
“…They reinforced the advantage of reduction and the practice of miniplate use for the fixation of zygomatic fractures in avoiding sensory deficit of the infraorbital nerve. 23 Our study was consistent with recovery of infraorbital nerve dysfunction following zygomatic fractures were recovery in 74% patients treated with open reduction within 12 weeks.…”
Section: Discussionsupporting
confidence: 89%
“…To date, no studies have reported sex differences in gene expression levels following trigeminal nerve injury. However, there is a case to be made for individually studying the trigeminal system (Benoliel et al., ; Arap et al., ; Prachur et al., ) and for inclusion of females in pain studies (Mogil and Chanda, ; Mogil, ). Addressing sex bias in pain research will increase translational relevance of preclinical findings.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the orbital floor fractures lie across the infraorbital foramen and canal. 11 The frequency of association with infraorbital nerve injury has been reported by Sakavicius et al 8 as 64.4% and by Schilli as 95%. 12 Fig.…”
Section: Discussionmentioning
confidence: 92%